1990
DOI: 10.1002/jbm.820240305
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal properties of a titanium‐peroxy gel obtained from metallic titanium and hydrogen peroxide

Abstract: A stable titanium-peroxy-radical complex is formed when metallic titanium interacts with hydrogen peroxide. The radical appears as one component in an aqueous gel formed when excess peroxides have been (catalytically) decomposed. The interaction between titanium and hydrogen peroxide may be of importance also in vivo during an inflammatory response at the implant. We report in this paper on the bactericidal effects of the titanium gel in the lacto- and myeloperoxidase-halogen systems. Escherichia coli viable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…This is attributed to the slow degradation and release of surface bound superoxide and peroxides known to occur in Ti-peroxide systems, resulting in a bactericidal effect. 43,44 Such inherent bactericidal action is not expected to occur on other TiO 2 surfaces produced by alternate means such as physical vapor deposition, sol-gel or anodic oxidation unless specifically loaded with antibiotics or other antimicrobial agents such as silver. 45 A gradual decline in activity, which indicates the release and effect of surface bound peroxides from H 2 O 2 -oxidized Ti-based substrates, accelerated under UV irradiation, was reported in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the slow degradation and release of surface bound superoxide and peroxides known to occur in Ti-peroxide systems, resulting in a bactericidal effect. 43,44 Such inherent bactericidal action is not expected to occur on other TiO 2 surfaces produced by alternate means such as physical vapor deposition, sol-gel or anodic oxidation unless specifically loaded with antibiotics or other antimicrobial agents such as silver. 45 A gradual decline in activity, which indicates the release and effect of surface bound peroxides from H 2 O 2 -oxidized Ti-based substrates, accelerated under UV irradiation, was reported in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies (1, 2) have found an antibacterial activity of ions from dental implants, including titanium, on various oral bacteria. Furthermore, it has been claimed that a titanium-peroxy gel posses.ses both antibacterial and anti-inflammatory properties in vitro (17), Whether such a titaniumperoxy gel is formed at all in vivo remains, however, to be proven. Many metals and alloys are used as dental restorations, and their effect on oral bacteria would presumably interfere with bacterial acquisition and plaque formation on such surfaces.…”
mentioning
confidence: 99%
“…28 It has been suggested that as a result of these mechanisms titanium acquires anti-inflammatory and, at the surface, antimicrobial properties by the formation of bactericidal titanium peroxy compounds. 29 Our results for subcutaneous and interstitial implants indicate that polyethylene as a biomaterial induces more inflammation than titanium as measured by the numbers of inflammatory cells at the interface. The effects of simultaneous adjuvant arthritis are not clear which may be due to the fact that the inflammation is more pronounced in the synovial tissue than other tissues.…”
Section: Discussionmentioning
confidence: 60%